Rural-urban differences in adult life expectancy in Indonesia: a parametric g-formula-based decomposition approach - Sudharsanan, Nikkil; Ho, Jessica Y. (Epidemiology, 2020)
BACKGROUND: Evidence on rural-urban differences in adult mortality in low- and middle-income countries (LMICs) is limited and mixed. We examined the size of and factors contributing to rural-urban life expectancy differences among adults in Indonesia, the third most populous LMIC. - METHODS: Data come from the 2000, 2007, and 2014/2015 waves of the Indonesian Family Life Survey, a population-representative longitudinal study with mortality follow-up. We used Poisson regression and life tables to estimate rural-urban differences in life expectancy among 18,867 adult respondents ≥30 years. We then used a novel g-formula-based decomposition to quantify the contribution of rural-urban differences in blood pressure (BP), body mass index (BMI), and smoking to life expectancy differences. - RESULTS: Compared with urban adults, life expectancy at age 30 was 2.2 (95% confidence interval [CI] = 0.4, 3.9) years higher for rural men and 1.2 (95% CI = -0.4, 2.7) years higher for rural women. Setting the BMI and systolic BP distribution equal in urban and rural adults reduced the urban mortality penalty by 22% for men and 78% for women, with the majority of this reduction coming from the contribution of rural-urban differences in BMI. Smoking did not contribute to the urban mortality penalty for either men or women. - CONCLUSIONS: Adult life expectancy is lower in urban than in rural areas in Indonesia and we estimate that this difference is partly related to differences in BMI and systolic BP.
Gesehen am 28.05.2020